TAFSIR MAQASIDI: PENAFSIRAN AL-QURAN BERBASIS MAQASID AL-SYARIAH
This paper will present a new perspective in understanding the Quran, which is the interpretation of the Quran which is oriented towards achieving the purpose of the shari’a. Contemporary scholars call it the ‘at-tafsi>r al-maqa>s